Case Report: Late coronary complication of Kawasaki disease - Bucher, Inès; Cook, Stéphane; Brahim Mathiron, Amel (Frontiers in Pediatrics, 2025)
Kawasaki disease, a common cause of acquired heart disease in children, can lead to long-term cardiovascular complications such as coronary aneurysms and stenosis. This case describes a 17-year-old male with a past medical history of Kawasaki disease at ages 3 and 8, treated with IV immunoglobulin leading to a moderate right coronary aneurysm, who presented for a cardiac check-up. He reports only a slight dyspnoea on exertion and atypical chest pain. Despite normal findings on routine ECG and exercise tests, advanced imaging revealed significant coronary stenosis requiring angioplasty. This highlights the limitations of standard diagnostic modalities and underscores the importance of multimodal imaging and tailored management strategies in such patients.